Analysis of CCR3 expression in corneal neovascularization in a murine model and human corneas. (August 2020) - Haber, Alberto; Polania-Baron, Eduardo J.; Bolaños-Jimenez, Rodrigo; Navas, Alejandro; Graue Hernandez, Enrique O.; Garfias, Yonathan
Abstract: The aim of this study was to examine the expression of the cytokines and chemokines receptor-3 (CCR3) molecule in endothelial cells and vascular structures in a murine model of corneal neovascularization and in samples of neovascularized human corneas. An immunofluorescence assay using the murine model showed a greater proportion and intensity of CCR3 in the epithelium and corneal subepithelial regions in corneas with neovascularization. In the absence of vascularization, no CCR3 was found. Of the 32 studied tissues, eight were vascularized and 24 were avascular. In the human corneas, vascularized corneas showed positive labeling for CD31 in all the analzedtissues, as well as positive labeling for CCR3. Therefore, all vascularized tissues showed positive coexpression of CCR3 and CD31, whereas none of the avascular corneas showed immunolabeling for either of these receptors. These results suggest that CCR3 could be a possible marker for corneal neovascularization with potential to be a therapeutic target. Highlights: CCR3 receptor is present in vascularized corneal tissue. There is a CCR3-CD31 colocalization in corneal neovessels. There is discrete expression of eotaxin−3 in neovascularized corneas.